Croatian radical separatism and diaspora terrorism during the Cold War - Tokić, Mate Nikola (Central European studies, 2020)
Cover -- Copyright -- Contents -- Acknowledgments -- List of Acronyms -- Introduction: Our Position Is Clear -- Chapter 1: There Can Be No More Discussion, 1948-1956 -- Chapter 2: In Contradiction to Sociopolitical Norms, 1956-1960 -- Chapter 3: The Facts as They Exist, 1960-1962 -- Chapter 4: All Accounts Have Not Yet Been Settled, 1962-1969 -- Chapter 5: We Have Chosen No One but Ourselves, 1969-1972 -- Chapter 6: Simply, It Comes Down to This, 1972-1980 -- Epilogue: Fixated for Many Years on This Day, 1980-1991 -- Notes -- Bibliography -- Index -- About the Author